Research-informed teaching: a clinical approach. Issue 1 (2nd January 2017) - Nicholson, Alex
ABSTRACT: In a bid to attract students amidst increasing competition within the sector, many universities claim that their teaching is "research-informed". However, there is some disagreement amongst academics about what actually counts as research-informed teaching and therefore how it should be developed and delivered. Furthermore, whilst academic reputation is a key factor for prospective university applicants, the primary objective of the majority is to enhance employability. Institutions must therefore be careful to ensure that research-informed teaching is developed in a way that is perceived to help rather than hinder this fundamental objective. This article seeks to define research-informed teaching and then considers whether clinical approaches to both teaching and research can offer more widely applicable strategies for effective integration of the two. Two case studies are considered: first, the writer's own experience as a solicitor in private practice; and secondly, Hallam Law, Sheffield Hallam University's pro bono law clinic. It is submitted that by adopting a clinical approach to the research and teaching on more orthodox, academic modules, it may be possible to develop and deliver research-informed teaching in a way that enhances employability and therefore appeals to prospective law students.